PENGUKURAN STATUS KAWASAN INDUSTRI TERHADAP KONSEP ECO INDUSTRIAL PARK - Hermawan Prasetya (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Scarcity of resources and environmental quality degradation stimulatedgovernment policy toward a new concept of Eco-Industial Park inmanaging and developing industrial estate in Indonesia. For applyingthe concept of EIP need conducted measurement of recent industrialestate status to EIP. This Article aim to develop a measurementinstrument and to measure some selected industrial estates.Measurement using developed instrument indicate that most industrialestastes have low status. The low status is generally influenced by thelowering of value at enviromental management and product exchangeindicators.